Bank Market Power and Firm Finance: Evidence from Bank and Loan Level Data (2019)
We present new measures of market power for the banking industry in Colombia and estimate their effect on the cost of credit for non-financial firms. Our results suggest that bank competition increased during the 2006-2008 period even as concentration increased but decreased thereafter. Using a unique combination of loan, firm and bank-level data sets we are also able to show that banks loosing overall market power –measured by the average price-cost margin– decrease interest rates to small firms, but increase rates to firms with which they have the oldest credit relationships. This suggests (i) the existence of market power that is specific to the bank-firm re lationship (i .e., informa-tional lock-in and hold-up problems due to switching costs), and (ii) that size may be capturing other firm attributes such as observable risk, scale effects or implicit collateral.